P514 LatchOn: A multi-centre, randomised controlled trial of perinatal support to improve breastfeeding outcomes in women with overweight and obesity. (June 2019) - O'Brien, Eileen; O'Reilly, Sharleen; Sheehy, Lucille; O'Hagan, Lorraine; McGuinness, Denise; Coughlan, Barbara; O'Brien, Denise; Murtagh, Rosie; Corbett, Marie; Walsh, Michelle; Power, Paula; Woodcock, Marie; et al.
Abstract : Background: Breastfeeding rates in Ireland are among the lowest worldwide. At hospital discharge, 58% of infants are breastfed, with only 48% exclusively breastfed. At 3 months of age, 35% are fed any breastmilk. Women with a high BMI have lower initiation rates and duration of breastfeeding, which is a particular concern in Ireland given that 50% of women have a BMI of >25 kg/m² at their first antenatal appointment. Objective: The aim of the intervention is to improve breastfeeding rates using a previously-tested, multi-component intervention. The intervention will target attitudes toward breastfeeding, breastfeeding self-efficacy, and subjective norms around infant feeding with the aim of normalising the behaviour. Methods: This protocol is for a multi-centre, randomised controlled trial of perinatal breastfeeding support among women with a BMI >25 kg/m². Hospital discharge data, validated questionnaires and qualitative interviews will be used to measure outcomes and intervention effectiveness. Ethical approval has been sought and recruitment will commence in early 2019. Patients: Primiparous women attending the study site hospitals with a singleton pregnancy and BMI >25 kg/m². Intervention: The intervention will target mothers and their support partners and will span the perinatal period from late pregnancy to six weeks postpartum. Intervention components include: group antenatal education for prospective mothers and their support partners; individual education in the immediate postnatal period; professional support to six weeks postpartum; and weekly phone calls in the postpartum period from an International Board-Certified Lactation Consultant. The primary outcome is prevalence of breastfeeding at 3 months. Results: We anticipate that the intervention will be well-accepted and feasible to carry out within an Irish cohort based on results from the pilot trial among 100 women. Furthermore, essential formative qualitative work has been conducted to inform the intervention design and to ensure that it is contextually appropriate. Conclusions: The proposed intervention will be invaluable to policy-makers as it will provide insights into the specific interventions (e.g. antenatal group education, antenatal individual education, postpartum support) that are effective in improving breastfeeding rates for women with a raised BMI and will highlight the measures that would be most cost-effective to implement nationally.